The Effect of Internal Control Mechanism Towards Fraud Prevention in Small and Medium Enterprises - Azwa Fariza Azizan; Mazurina Mohd Ali (Indonesian Journal of Sustainability Accounting and Management, 2024)
The aim of this study is to examine the effects of internal control mechanism namely, control environment, control activities, risk assessment, information and communication, and monitoring activities on the fraud prevention amongst employees in SMEs. The study used quantitative method to collect data by distributing a questionnaire to 131 SME owners from various SME sectors to achieve the study's objectives. Using regression analysis, the results obtained on the internal control mechanism of SMEs revealed that all the independent variables, namely, control environment, control activities, risk assessment, information and communication, and monitoring activities have substantial roles to safeguard SMEs business against fraudulent activities by the employees. This study would benefit business owners to assess the organization’s internal control mechanism that can prevent, detect, or minimise any attempted wrongdoing by employees. The value of this study lies in its contribution to understanding and enhancing fraud prevention mechanisms within SMEs. The specific aspects investigated—control environment, control activities, risk assessment, information and communication, and monitoring activities—provide valuable insights into the internal control systems of SMEs and their effectiveness in mitigating fraudulent activities by employees.